Implementation of Village Budget Management Policies In An Effort to Improve The Welfare of Village Communities in Klaten District - Sarida Minarni; Paiman Raharjo; Triyuni Soemarono; Khasan Effendy; T.Herry Rachmatsyah (Coopetition)
Research of Village Fund for 2024. Government Agency which has  Klaten Regency Empowerment Service a an were  meanwhile, data analysis techniques are data reduction, data display, conclusion drawing.Research show Management Klaten  has  carried out  the Klaten Regency Regulation  2022 concerning the Klaten Regent Regulation  92 of 2019 Guidelines for Implementing Village Fund Allocation Management. However, in practice, relatively not all work is carried out in an administrative order. Meanwhile, implementation factors are financial. They meanwhile management disposition, it needs to be considered.